2007
DOI: 10.22452/adum.vol14no1.8
|View full text |Cite
|
Sign up to set email alerts
|

Impact strength of an experimental polyurethane- based polymer

Abstract: The impact strength of a newly developed experimental polyurethane-based polymer which is derived from palm oil (Experimental PU) was compared with denture polymers; heat-cured and self cured polymethyl methacrylate (PMMA) and Eclipse ® , light-activated urethane dimethacrylate prosthetic resin system. Ten specimens were prepared using heat-cured PMMA (Meliodent ® Heat Cure, Heraeus Kulzer, Germany), self cured PMMA (Meliodent ® Rapid Repair, Heraeus Kulzer, Germany), Eclipse ® baseplate resin (Dentsply, USA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Polyurethanes are segmented polymers that have both soft and hard segments, providing both flexibility and toughness characteristics 4 . In a urethane dimethacrylate polymer, the long aliphatic polyether segment in the repeated unit provides improved chain flexibility, which may explain the improved toughness of urethane dimethacrylate‐based materials 4 . Some commercially available aliphatic urethane dimethacrylate polymers have shown significantly higher flexural strengths than other resins 22 with the increased strength attributed to the lower molecular weight and molar volume of urethane dimethacrylate resin monomers that would increase the initial methacrylate functionality of the unpolymerised resin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethanes are segmented polymers that have both soft and hard segments, providing both flexibility and toughness characteristics 4 . In a urethane dimethacrylate polymer, the long aliphatic polyether segment in the repeated unit provides improved chain flexibility, which may explain the improved toughness of urethane dimethacrylate‐based materials 4 . Some commercially available aliphatic urethane dimethacrylate polymers have shown significantly higher flexural strengths than other resins 22 with the increased strength attributed to the lower molecular weight and molar volume of urethane dimethacrylate resin monomers that would increase the initial methacrylate functionality of the unpolymerised resin.…”
Section: Discussionmentioning
confidence: 99%
“…12 reported that Microbase, which is also a polyurethane polymer base, had a mean impact strength value of 6.3 kj/m 2 . Only one study evaluated the impact strength of Eclipse resin 4 , and the mean value obtained was 2.73 kj/m 2 . It has been reported that depending on the loading configuration (Izod or Charpy), the specimen dimensions and the presence of notches and their geometry, the impact test can result in different values of impact strength 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Although flexural stresses that are counteracted by the flexural strength of the material are a constant phenomenon during mastication, impact strength is also required to prevent accidental dropping or falling of the dentures. Because dentures have frenal notches and some scratches on the denture surface that act as common stress concentrated areas and consequently reduce the strength of the dentures, 31 a Charpy-type impact test was selected for this study, and V-shaped notches were created in the specimens in order to simulate denture borders.…”
Section: Gad Et Almentioning
confidence: 99%
“…The existence of a V-notch confirmed that the specimens were broken at the same point during testing. 31,42 Therefore, the surface design did not significantly affect the repairs' impact strength.…”
mentioning
confidence: 96%
“…Also, the effect of alumina (Al 2 O 3 ) addition has been reviewed and reported a positive impact on the properties of acrylic resin (38) . Although flexural stresses that are counteracted by the flexural strength of the material are a constant phenom enon during mastication, impact strength is also required to prevent fracture upon accidental dropping or falling of the dentures (39) .…”
Section: Introductionmentioning
confidence: 99%